Inhalasi Whipping Pink (Nitrous Oxide) Terhadap Kegawatan Neurologis–Respiratorik: Analisis Misinformasi Media Sosial Dalam Perspektif Keperawatan Kritis - Rivani Nur Oktavia; Regyta Marshanda; Budi Widiyanto (Universitas Pahlawan Tuanku Tambusai, 2026)
Whipping pink inhalation (recreational Nitrous oxide/N₂O) is increasingly popular on social media and is often perceived as safe. However, repeated exposure can trigger neurological emergencies such as peripheral neuropathy, myelopathy due to vitamin B12 deficiency, and respiratory disorders in the form of acute hypoxia and respiratory depression. Digital misinformation has the potential to delay detection and management in critical care. This study aims to analyze the clinical impact of N₂O inhalation on neurological and respiratory emergencies and analyze social media misinformation from a critical care nursing perspective. The method used is an Evidence Based Practice-based literature analysis through a review of the latest scientific journals related to the effects of N₂O toxicity, clinical manifestations, and implications for critical care nursing. The results show that chronic exposure to N₂O inactivates vitamin B12, causing spinal cord demyelination, sensorimotor disorders, and the risk of hypoxia due to oxygen displacement. Early intervention, screening of use history, and evidence-based education are crucial. It was concluded that recreational N₂O inhalation carries a high risk of neurological and respiratory emergencies. Critical care nurses play a strategic role in early detection, stabilization, and education to counter misinformation.